Linking suburban youth in Madrid and Paris. The role of civil society structures in the integration of children from Muslim backgrounds. (October 2019) - Eseverri Mayer, Cecilia
This comparative study focuses on how civil society structures influence youth from a Muslim background in their upward mobility and local belonging (to the neighbourhood and to the city). Under comparison are one banlieue in Paris and one barrio in Madrid, similar in terms of social precarity and yet different in their degree of ethnic and religious diversity, their connection to the city centre, the state funding they receive and their civic participation. In the case of the neighbourhood of San Cristóbal (Madrid), a lack of state investment has resulted in a diminished capacity for civil society to connect young people to new opportunities. However, their daily contact with the city centre, the ethnic diversity in the neighbourhood and collaborative efforts between secular and religious structures work together to foster a sense of mixed belonging among young Spanish Muslims. In contrast, significant investment by the State in the suburb of Les Bosquets (Paris) since the riots in 2005 have indeed linked young people to new opportunities, but at the cost of an institutionalisation of civil society structures. In Les Bosquets, increased ethnic segregation, geographical isolation, and the estrangement of religious and 'laic' (i.e. secular) organisations are all responsible for the new sense of malaise felt by youths, thus severely affecting their sense of belonging.